ENACTING GEMEINDE IN THE LANGUAGE OF STORY: NARRATIVE PERFORMANCE AMONG KANSAS MENNONITES FROM VOLYN - McCabe-Juhnke, John (Psychological Prospects Journal, 2015)
This article examines oral narrative performance within the cultural context of the Swiss Volynian Mennonites in Moundridge, Kansas, whose forbears were members of a congregational group that migrated from Volyn Province in Polish Russia in 1874. A Swiss Volynian Mennonite himself, the author tape-recorded interviews with second and third generation descendants of the Mennonites from Volyn. Using interview transcriptions and participant observation in the Moundridge community as primary data, the author analyzes how the language of storytelling performance both sustains and is shaped by social and cultural norms of Swiss Mennonite Gemeinde. An analysis of the personal and social roles of Swiss Volynian storytellers reflects a fundamental tension between individuality and conformity. Swiss Volynians most frequently perform at the level of natural or unself-conscious narration rather than intentional or public narration, allowing oral narrators to maintain the community norm of self-effacement despite their obvious competence as storytellers. An examination of the written transcriptions of these oral narratives reveals noticeable contextual overtones. The use of dialect, insider’s code and community-oriented genres demonstrates the storytellers’ evocation of an in-group context for storytelling